Scientometric Dimensions of Thorium Research in lndia - Kademani, B.S.; Kumar, Vijai; Sagar, Anil; Mohan, Lalit; Surwase, Ganesh (DESIDOC Journal of Library & Information Technology, 2006)
This paper attempts to provide detailed quantitative analysis of lndian contributions on thorium in terms of publications output as per International Nuclear lnformation System database during 1970-2004. A total of 2399 papers were published by the lndian scientists in the field of thorium. There were only nine publications in 1970. Thereafter, a steady growth was observed except for the period 1983-1985. The highest papers (188) ware published in the year 2000. USA with 8049 (28.05 per cent) and lndia with 2399 (8.30 per cent) publications were the top two countries who published work on thorium. Authorship and collaboration trend was towards multi-authored papers as 85.70 per cent of the papers were collaborative. There were 79 international collaborative papers. Bilateral collaboration accounted for 90.14 per cent of total collaborative papers. Bhabha Atomic Research Centre, Mumbai topped the list with 1251 authorships followed by lndira Gandhi Centre for Atomic Research, Kalpakkam with 168, Atomic Minerals Division, Hyderabad with 71, Utkal University, Bhubaneswar with 43 and Saha Institute of Nuclear Physics, Kolkata with 31 authorships, respectively. The journals most preferred by the scientists for publication of papers were: Journal of the lndian Chemical Society with 78 papers, followed by the lndian Journal of Chemistry A with 60 papers, Bulletin of Radiation Protection with 56 papers, Journal of Radio Analytical and Nuclear Chemistry with 54 papers, Radiation Protection and Environment with 37 papers, Exploration and Research for Atomic Minerals and Journal of Geological Society of lndia with 35 papers each. English was the most predominant language used by the scientists for communication. The high frequency keywords were: thorium (559), uranium (316), thorium oxides (269), lndia (257), solvent extraction (236), quantitative chemical analysis (221) and thorium 232 (202). http://dx.doi.org/10.14429/dbit.26.3.3683